Older Adults’ Vigorous Occupational Physical Activity Levels in Six Countries Are Explained by Country and ‘Having Multiple Jobs’ - Villalobos-Dintrans, P (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Several studies have compared physical activity (PA) levels between countries, but none of these studies focused on older adults and occupational PA. This study aimed to assess potential inequalities in older adults’ occupational PA across six countries and to ascertain whether having multiple jobs is a factor that interacts with country of residence to modify inequalities. This study adopted a cross-sectional design with a statistical technique screening for potential covariates. Older adults (mean age = 64 years; range = 50–114 years) from six countries (Russia, Mexico, China, India, Ghana, and South Africa) participated in the study. We utilised data from the first wave of the Study on Global AGEing and Adult Health (SAGE). These data were collected from 2007 to 2010. A random sample of 34,114 older adults completed the survey. We analysed the data with a two-way multivariate analysis of variance after screening for the ultimate covariates. There were differences in occupational PA levels (i.e., vigorous and moderate PA) among the six countries. Occupational PA levels were not significantly associated with having multiple jobs. However, having multiple jobs interacted with country of residence to influence vigorous occupational PA. Older adults from most countries who had more than one job reported more vigorous occupational PA. Older adults’ occupational PA differed among the six countries, and having multiple jobs was associated with more vigorous occupational PA. Older adults who keep multiple jobs at a time may be more active than their counterparts who had one job or were unemployed. © 2022 by the authors.